Development and validation of RP – HPLC method for the estimation of Tylosin tartrate in pure and pharmaceutical formulation - Sailaja Kotha; N.Sunitha; S.Manoharbabu. (International Journal of Pharmacy and Analytical Research, 2014)
A simple, fast, precise, selective and accurate RP-HPLC method was developed and validated for the simultaneous determination of tylosin tartrate from pharmaceutical formulation. Chromatographic separation was achieved gradient on a phenomenex c18 column (250 x 4.6 mm, 5 µ particle size) using a mobile phase. Acetonitrile and water in the ratio of 90:10.the flow rate was 1.5ml / min and effluent was detected at 292 nm. The retention time of tylosin tartrate was found to be 2min. linearity was observed in the concentration range of 50 -250µg /ml. The method was validated according to ICH guidelines with respect to specificity, linearity, accuracy, precision and robustness. The method developed can be used for the routine analysis of tylosin tartrate.